Connecticut Connections: African American Sites in Connecticut: A Laboratory for the History of Slavery and Human Rights - Forbes, Robert P. (Connecticut History Review, 2005)
Keywords: dept.his; ⛔ No DOI found

Eliade, Joyce, and the Terror of History - Forbes, Robert P. (CrossCurrents, 1986)
Keywords: dept.his; ⛔ No DOI found

The Missouri Compromise and Its Aftermath: Slavery and the Meaning of America - Forbes, Robert P. (University of North Carolina Press, 2007)
Robert Pierce Forbes goes behind the scenes of the crucial Missouri Compromise, the most important sectional crisis before the Civil War, to reveal the high-level deal-making, diplomacy, and deception that defused the crisis, including the central, unexpected role of President James Monroe. Although Missouri was allowed to join the union with slavery, the compromise in fact closed off nearly all remaining federal territories to slavery.When Congressman James Tallmadge of New York proposed barring slavery from the new state of Missouri, he sparked the most candid discussion of slavery ever held in Congress. The southern response quenched the surge of nationalism and confidence following the War of 1812 and inaugurated a new politics of racism and reaction. The South's rigidity on slavery made it an alluring electoral target for master political strategist Martin Van Buren, who emerged as the key architect of a new Democratic Party explicitly designed to mobilize southern unity and neutralize antislavery sentiment. Forbes's analysis reveals a surprising national consensus against slavery a generation before the Civil War, which was fractured by the controversy over Missouri.
Keywords: dept.his

'Truth Systematised’: The Changing Debate over Slavery and Abolition - Forbes, Robert P. (Prophets of Protest: Reconsidering the History of American Abolitionism, 2006)
The first collection of original contributions on American abolitionism to appear in a generation.The campaign to abolish slavery in the United States was the most powerful and effective social movement of the nineteenth century and has served as a recurring source of inspiration for every subsequent struggle against injustice. But the abolitionist story has traditionally focused on the evangelical impulses of white, male, middle-class reformers, obscuring the contributions of many African Americans, women, and others.Prophets of Protest, the first collection of writings on abolitionism in more than a generation, draws on an immense new body of research in African American studies, literature, art history, film, law, women's studies, and other disciplines. The book incorporates new thinking on such topics as the role of early black newspapers, anti-slavery poetry, and abolitionists in film and provides new perspectives on familiar figures such as Sojourner Truth, Louisa May Alcott, Frederick Douglass, and John Brown.With contributions from the leading scholars in the field, Prophets of Protest is a long overdue update of one of the central reform movements in America's history.
Keywords: dept.his

"Foreword," special issue on "New Perspectives on the Transatlanic Slave Trade - Forbes, Robert P.; Davis, David Brion (William & Mary Quarterly, 2005)
Keywords: dept.his; ⛔ No DOI found

Trust and Violence in Atlantic History: The Economic Worlds of Venture Smith - Forbes, Robert P.; Richardson, David; Chandler, B. Saint (Venture Smith and the Business of Slavery and Freedom, 2010)
Keywords: dept.his

The Missouri Controversy and Sectionalism - Forbes, Robert P. (Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson, 2008)
In 1815 the United States was a proud and confident nation. Its second war with England had come to a successful conclusion, and Americans seemed united as never before. The collapse of the Federalist party left the Jeffersonian Republicans in control of virtually all important governmental offices. This period of harmony—what historians once called the Era of Good Feeling—was not illusory, but it was far from stable. One-party government could not persist for long in a vibrant democracy full of ambitious politicians, and sectional harmony was possible only as long as no one addressed the hard issues: slavery, race, western expansion, and economic development.Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson inaugurates a new series for the United States Capitol Historical Society, one that will focus on issues that led to the secession crisis and the Civil War. This first volume examines controversies surrounding sectionalism and the rise of Jacksonian Democracy, placing these sources of conflict in the context of congressional action in the 1820s and 1830s. The essays in this volume consider the plight of American Indians, sectional strife over banking and commerce, emerging issues involving slavery, and the very nature of American democracy.“It is to be regretted that the rich and powerful too often bend the acts of government to their selfish purposes…. There are no necessary evils in government. Its evils exist only in its abuses. If it would confine itself to equal protection, and, as Heaven does its rains, shower its favors alike on the high and the low, the rich and the poor, it would be an unqualified blessing. In the act before me there seems to be a wide and unnecessary departure from these just principles.”—Andrew Jackson, Veto Message Regarding the Bank of the United States, July 10, 1832“I consider, then, the power to annul a law of the United States, assumed by one State, incompatible with the existence of the Union, contradicted expressly by the letter of the Constitution, unauthorized by its spirit, inconsistent with every principle on which it was founded, and destructive of the great object for which it was formed.”—Andrew Jackson, Proclamation Regarding Nullification to the People of South Carolina, December 10, 1832
Keywords: dept.his

Abolition and Antislavery: United States - Forbes, Robert P. (A Historical Guide to World Slavery, 1998)
Eminent scholars provide an overview of what we now know about slavery as an institution and way of life in cultures around the globe from ancient times to the present day. Drawing on the virtual explosion of empirical research and theoretical discussion on the subject over the past thirty years, many of the articles overturn conventional wisdom and illuminate little-known aspects of the subject, with essays on topics such as concubinage, eunuchs, and occupational mobility.
Keywords: dept.his

Francis Kernan: The Life and Times of a 19th Century, Citizen-Politician of Upstate New York - Kernan, Karen Clemens; Kernan, John Devereux; Forbes, Robert P. (Oneida County Historical Society, 1999)
Keywords: dept.his